(untitled) (Journal of Global Accounting, 2023)
This study ascertained the relationship between social responsibility disclosure and sustainable development of quoted industrial firms in Nigeria. Fourteen (14) quoted industrial firms constituted the sample size of this study between 2011 and 2021. Ex-Post facto research design and content analysis were adopted while secondary data were extracted from the annual reports and accounts of the sampled firms and were analysed using E-Views 10.0 statistical software. The study employed descriptive statistics and inferential statistics using Pearson correlation and Binary Probit regression analysis. Three hypotheses were formulated and statistically tested at 5 per cent level of significance using regression analysis. Findings from the empirical analysis showed that a significant and positive relationship exists between environmental social responsibility disclosure and waste recycling (β1 = 0.829307; p-value = 0.0000<0.05); a significant and positive relationship exists between ethical social responsibility disclosure and waste recycling (β2 = 0.746503; p-value = 0.0000<0.05); a significant and positive relationship exists between philanthropic social responsibility disclosure and waste recycling (β3 = 0.022601; p-value = 0.0418<0.05) of quoted industrial goods firms in Nigeria at 5% level of significance. Consequently, this analysis supports growing evidence that social responsibility disclosure have a significant relationship and exerts significant influence on sustainable development at 5% significant level. The study further concludes that the components of social responsibility disclosure considered in this study are important variables in explaining sustainable development of quoted industrial firms in Nigeria. It was recommended inter alia that firms should be environmentally friendly to enable them gain competitive advantage, high liquidity and reduced environmental cost in the long run, thereby leading to a sustainable development.